Design Of A Web-Based Patient Complaints Service Project Management Information System At Tarogong Health Center - Rosliani, Elin; Budiman, Tedi; Dewi Yanti, Lina (RISTEC : Research in Information Systems and Technology, 2024)
This study addresses the development of a web-based patient complaint management system at Puskesmas Tarogong. The aim is to facilitate patients in submitting complaints about the services they receive, thus improving the overall quality of healthcare services. Traditional complaint processes often require significant effort and time from patients, such as physically visiting the healthcare facility and waiting for responses. The proposed system allows patients to submit and track complaints in real-time, from anywhere and at any time, without the need for a physical visit. This system also enables healthcare staff to respond to complaints more efficiently, thereby enhancing patient satisfaction. Furthermore, real-time access to complaint data helps Puskesmas Tarogong identify areas needing improvement and take appropriate measures to enhance their services. The implementation of this system is expected to significantly improve the quality of healthcare services by ensuring effective and efficient complaint handling. Keywords : web-based system, patient complaints, healthcare service quality, real-time tracking, Puskesmas Tarogong, efficiency, patient satisfaction.